2009
DOI: 10.1111/j.1600-0706.2009.17621.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinks without borders: snowshoe hare dynamics in a complex landscape

Abstract: A full understanding of population dynamics of wide‐ranging animals should account for the effects that movement and habitat use have on individual contributions to population growth or decline. Quantifying the per‐capita, habitat‐specific contribution to population growth can clarify the value of different patch types, and help to differentiate population sources from population sinks. Snowshoe hares, Lepus americanus, routinely use various habitat types in the landscapes they inhabit in the contiguous US, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 49 publications
7
87
1
Order By: Relevance
“…As animals died, new individuals were radiocollared, year-round and throughout the study. Wild snowshoe hares generally have low annual survival rates (17,35), limiting the expression of individual plasticity across >1 y. Of our 148 different animals monitored, only 7 survived for >1 fall or spring molt and only one survived for >1.5 y after collaring; because of incomplete detection and temporary emigration of radiocollared animals, we were not able to document consecutive spring or fall molts for any of these 7 hares.…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…As animals died, new individuals were radiocollared, year-round and throughout the study. Wild snowshoe hares generally have low annual survival rates (17,35), limiting the expression of individual plasticity across >1 y. Of our 148 different animals monitored, only 7 survived for >1 fall or spring molt and only one survived for >1.5 y after collaring; because of incomplete detection and temporary emigration of radiocollared animals, we were not able to document consecutive spring or fall molts for any of these 7 hares.…”
Section: Methodsmentioning
confidence: 86%
“…Hare densities in this region vary but tend to be less than two hares per ha (34). Snowshoe hares were livetrapped using Tomahawk traps (Tomahawk Live Trap Company, Tomahawk, WI) and fitted with radiocollars (Wildlife Materials, Murphysboro, IL) (17). All handling procedures were in accordance with the University of Montana Institutional Animal Care and Use Committee animal use protocol (Protocol no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Wilcove (1985) observed elevated nest predation rates on very small forest fragments and on patches closer to suburban areas. Accordingly, some snowshoe hare studies have found increased predation in open areas with reduced cover (Dolbeer 1975, Sievert and Keith 1985, Griffin and Mills 2009, while others have found predation to be very high on small patches of habitat in highly fragmented landscapes (Keith et al 1993, Wirsing et al 2002.…”
Section: Table Of Contents List Of Figuresmentioning
confidence: 99%